2017
DOI: 10.17221/161/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chromolaena odorata leaf extracts for the healing of rat excision wounds

Abstract: Injury to the soft tissues is followed by wound healing, which consists of four stages: haemostasis, inflammation, proliferation and remodelling. Chromolaena odorata is a weed that is traditionally used for the treatment of various ailments in humans and animals. The present study was aimed at exploring the wound healing potential of aqueous and ethanolic extracts of C. odorata in a rat excision wound model. This investigation involved phytochemical screening and in vitro analyses of various parameters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 51 publications
0
11
0
3
Order By: Relevance
“…Several extraction methods were previously used to recover phenolic compounds from C. odorata , including maceration, decoction, and Soxhlet , , . However, lower recovery yields of the phenolic compound from this plant were reported for these extraction methods; thus, microwave‐assisted extraction (MAE) has been employed herein to recover phenolic compounds from C. odorata leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Several extraction methods were previously used to recover phenolic compounds from C. odorata , including maceration, decoction, and Soxhlet , , . However, lower recovery yields of the phenolic compound from this plant were reported for these extraction methods; thus, microwave‐assisted extraction (MAE) has been employed herein to recover phenolic compounds from C. odorata leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it should be noted that increasing extraction temperature beyond a certain limit may cause concurrent degradation of phenolic compounds that would have been mobilized at a lower temperature. A higher extraction temperature can results in solvent loss through vaporization, this can increase the cost of the extraction process [10,12]. Previous reports by Ameer et al showed that the interaction between irradiation time and ethanol concentration, and irradiation time and microwave power enhanced the Reb-A from powdered stevia leaves [19].…”
Section: Influence Of Mae Parameters On the Tpc And Tfc Yields From Cmentioning
confidence: 99%
“…More so, it should be noted that increasing extraction temperature beyond a certain limit may cause concurrent degradation of phenolic compounds that would have been mobilized at a lower temperature. Likewise, a higher extraction temperature leads to solvent loss through vaporization, this can increase the cost of the extraction process [10,12]. In order to affirm the significant contribution of extraction temperature to this process, the extraction temperature in a range of 40 to 80 °C was chosen for further experimentation.…”
Section: One-factor-at-a-time Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a flowering shrub that is native to Central and North America, and was later introduced to Africa, Asia, and Australia [10]. C. odorata is known by other names such as baby tea, bitter bush, Armstrong's weed, butterfly weed, devil weed, king weed, Christmas bush, Siam weed, eupatorium, paraffin weed and turpentine weed [11]. It contains bioactive compounds such as steroids, flavonoids, alkaloids, tannins and saponins, which can act singly or synergistically to exert different biological effects [12].…”
Section: Acquisition Of Mice Parasites and Mice Inoculationmentioning
confidence: 99%